Patologías asociadas a la deficiencia de cobre y zinc que afectan al ganado bovino (2021)
At present, the study of micromineral deficiency in bovines has been an uncommon topic, and it has not been a specific objective in terms of bibliographic differentiation, but it has had a great boom in terms of type conservation. physiological and behavioral in terms of its pathogenesis and conditions in the reproductive field, so according to a review of a set of mineral studies such as copper and zinc are highly fundamental, and the lack of mineral homeostasis within the bovine organism can cause the presentation of different pathologies related to them, so their study is necessary, so it is possible to conclude that not only the lack of mineral contribution in the case of a research approach (Copper and Zinc) can produce this deficit, but also the presentation of antagonists, which are another set of minerals or compounds that in large quantities do not allow absorption and subsequently block the function of the mineral within the body of the animal causing alterations.